The People's Republic of China's Financial Policy and Regional Cooperation in the Midst of Global Headwinds - Iwan J. Azis (Asian Development Bank (ADB), 2013)
Although growth deceleration in the People's Republic of China (PRC) is inevitable, if the country's new direction of financial policy (on exchange rate, capital flows, banking, capital market) can be achieved, it will be good not only for the country but also for the rest of Asia. This is consistent with the increased degree of Asia's integration and interdependence. But given the nature of financial contagion and spillovers across countries and asset classes, the financial headwinds from global crisis may require regional cooperation in safety nets provision, as the domestic policy in the PRC and other Asian countries is likely insufficient. Equally essential is the cooperation among Asian regulators to secure financial stability and enhance market liquidity. If coordinated well, such cooperation can also strengthen Asia's collective voice to ensure that harmonization of international rules does not mean applying the same laws in all jurisdictions, and that the global debates on bank-centric regulations do not have adverse consequences on Asian capital markets.
hdl:11540/2316
Keywords: E52; E58; F31; F36; G15; G18; 330; PRC financial policy; global headwind; Asia interdependence; regional cooperation; financial regulation